UPAYA MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR SISWA MELALUI MODEL AUDITORY INTELLECTUALLY REPETITION (AIR) PADA MATERI ENERGI - Nurmansyah, Edy; Tandililing, Edy; Erwina, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study is to improve learning outcomes and student Â activities through the Auditory Intellectually Repetition model at the energy material. Classroom Action Research (CAR) conducted in two cycles. The subjects were students of class VIII C SMPN 5 Pontianak 2015/2016 academic year as many as 36 students. The data collection includes achievement test and activity of observation sheet. The data obtained showed an increase in student learning outcomes from the first cycle to the second cycle of 53% to 83%. The tests were given before and after the learning is determined by the percentage of classical completeness. The results of learning activities of students showing improvement, namely in the first cycle and the second cycle of active category 80% to 92%. These results indicate that the model of Auditory Intellectually Repetition can improve learning outcomes and student learning activities in a energy material.Â Keywords : Outcomes, Activities, AIR, Energy.Â